Utilization of The Qr-Code on The Santri Id-Card as The Santri’s Personal Data Code - M. Agung Vafky Ideal (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Data management has always been a challenge in all aspects, including the management of students' personal information. Building an information system capable of producing student Id-cards equipped with a QR-code enables the use of the QR-code on the student Id-card as a student personal data code. This study aims to build a system to make it easier to make student ID-cards, store personal data, and data on student semester scores. The QR-code on the student's ID card serves as a medium for quickly conveying information encoded with Uniform Resource Locators (URL). Santri can scan the QR-Code with a smartphone device that has a QR-code scanning app installed. The Research and Development (RnD) version of ADDIE was used in this study (Analyze, Design, Develop, Implement, Disseminate). The application was created with the sublimetext software, the codeigniter framework, and CSS bootstrap as the front end. For the validity test, Aiken's